(untitled) (Journal of Shaheed Suhrawardy Medical College, 2026)
Hepatic Resection is the first-line curative treatment in selected patients with benign as well as malignant liver lesion. Though due to refinement in surgical technique and peri operative care, the outcome of hepatic resection has been improved but mortality and morbidity still remains high in patient with chronic liver disease (CLD) specially post hepatectomy liver failure (PHLF). Various scoring system such as albumin bilirubin (ALBI), aspartate aminotransferase to lymphocyte ratio (APRI) has developed but they are difficult to calculate. Prognostic nutritional index (PNI) is calculated by serum albumin & total lymphocyte count. It is easy to calculate and cost effective, may not only reflect the nutritional status but also systemic inflammation. As a result, further research is needed whether prognostic nutritional index (PNI) is associated with the postoperative outcome after liver resection. Aim: To evaluate the value of preoperative prognostic nutritional index (PNI) to predict the postoperative outcome after liver resection. Methods: After receiving approval from the Institutional Review Board (IRB) of BSMMU, this study was conducted at the Department of Hepatobiliary, Pancreatic, and Liver Transplant Surgery, BSMMU, Dhaka. During the study period, a total of 34 consecutive patients were enrolled, who were undergone liver resection. After meeting inclusion and exclusion criteria, an informed written consent was obtained from each patient or from person authorized by the patient before their participation in this study. Prior to participation, all patients were evaluated using a combination of history, clinical examination, laboratory tests, and imaging techniques. Prognostic nutritional index (PNI) scoring was done after admission of patient selected for liver resection. Per operative information was collected. Routine hematological and biochemical investigations such as, white blood cell (WBC) count, hemoglobin percentage, serum albumin, serum bilirubin, serum creatinine, prothrombin time (PT), international normalized ratio (INR), serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate (SGOT) and alkaline phosphatase (ALP) were measured during the early post-operative days. The outcomes of surgery will be assessed and any post-operative complications that may happen were graded according to Clavien-Dindo classification and dealt accordingly. The association of prognostic nutritional index (PNI) was evaluated by observing postoperative complications such as infectious complications, length of hospital stays and post hepatectomy liver failure (PHLF). Results: It was observed that about 35% patients had hepaticolithiasis and 35% patients had GB mass followed by 5 (15%) HCC, 2 (6%) giant hemangioma, 2 (6%) FNH and 1(3%) simple hepatic cyst. Patients were divided into high PNI group and low PNI group. Demographic variables (age, sex, BMI) and associated comorbid conditions were similar between two groups of patients. There was no difference in types of liver resection between two groups. p value 0.859 per operative data showed operative time and whole blood transfusion were similar between two groups. On the other hand, amount of blood loss and FFP transfusion were different significantly showing p value 0.0475 and 0.0336 respectively. Comparison of postoperative outcomes and complications were similar between two groups. But in the length of hospital stay, we found significant differences between two groups. p value <0.01. Conclusion: This study demonstrates a relationship between preoperative nutritional and inflammatory parameters with postoperative outcomes in patients undergoing LR. J Shaheed Suhrawardy Med Coll 2024; 16(1): 43-48